Oxytocin predicts positive affect gains in a role-play interaction - Berceanu, Alexandru I.; Papasteri, Claudiu; Sofonea, Alexandra; Boldasu, Romina; Nita, Diana; Poalelungi, Cătălina; Froemke, Robert; Carcea, Ioana (Frontiers in Psychology, 2024)
Introduction Role-play, a key creative process in theatre, is used in therapeutic interventions to improve social skills, emotion regulation, and memory. Although role-play is widely used as a psychotherapeutic technique, its mechanisms of action are not fully understood. Methods Our study introduces a standardized controlled procedure for promoting role-play in the laboratory based on the portrayal of a fictional persona and examines its effects on anxiety, affect, prosocial attitudes, and salivary oxytocin dynamics in 38 participants. Results In our experiment, role-play significantly increased positive affect and prosocial attitudes and decreased anxiety compared to a control condition. Basal salivary oxytocin levels predicted higher gains in positive affect following role-play, suggesting a specific moderating effect of oxytocin. The fictional persona used in the procedure was rated as very happy by subjects, creating a positive social context for the role-play social interaction. Discussions We propose that the observed moderation effect of oxytocin in our study is specific to the role-play condition due to the capacity of role-play to generate an affective regulatory context based on congruency toward the emotional state of the fictional persona. Our findings indicate that basal oxytocin levels could predict specific outcomes of role-play in therapeutical setting. We discuss several psychological and biological mechanisms that could account for the observed effects of role-play and how oxytocin could act as a substrate for them.